Genome-wide identification of PSKR genes in wheat and differential expression under abiotic stress conditions - Ma, Zhenbing; Wei, Jingren; Zheng, Jia; Su, Jian; Zhao, Dong (Frontiers in Plant Science, 2025)
Phytosulfokine (PSK) is an important plant growth factor regulating plant stress response, PSKR gene family plays an important role in the PSK signaling pathway, but there are few reports in wheat (Triticum aestivum L.). In this study, 149 TaPSKR genes were identified by using hidden Markov models (HMMs) and sequence homology, and their evolutionary relationship, structural characteristics and stress regulation mechanism were systematically analyzed. Our results indicated that genes were unevenly distributed across 21 chromosomes of the wheat genome. Phylogenetic tree and conserved motif analysis revealed that the gene motifs, domains, and structures were relatively conserved, and 75.2% of TaPSKR genes clustered in one clade with monocotyledons. Chromosome distribution showed that genes were enriched in chromosomes 6A (20.13%), 6B (16.11%) and 6D (18.79%). A total of 6,463 cis-acting elements were discovered in the promoter regions of PSKR genes, indicating that these genes are regulated by various developmental, environmental, and hormonal factors, as well as light responses. Expression profile results demonstrated that these genes were influenced by various abiotic stressors, such as PEG6000, salt, cold, heat, and different hormones, including gibberellic acid, jasmonic acid, abscisic acid, 6-benzylaminopurine, and salicylic acid. Additionally, quantitative real-time PCR was performed to further confirm the transcriptomic data. TaPSKR genes may participated in abiotic stress response and phytohormone regulation pathway, which provided key gene resources and theoretical basis for the analysis of PSKR signaling pathway and molecular breeding for stress resistance in wheat.